PECULIAR FEATURES OF REGENERATION AT THE END OF BONE FILING AFTER AMPUTATION OF A LIMB - Shevchuk, V.I.; Bezsmertnyi, Y.O.; Bezsmertna, G.V.; Dovgalyuk, T.V.; Jiang, Y. (World of Medicine and Biology, 2020)
In order to evaluate the reparative processes at the end of the bone after amputation, 4 series of experiments were carried out on 64 rabbits with filing plastic cortical plate, its combination with miodesis, fascia cover and stitching of antagonist muscles. Timing of observation: 1, 3, 6 months. Examination method: histological with vessel filling in ink-gelatin mixture. It was established that in the first two series the formation of the bone closing plate and intraosseous circulation were restored by 1 month. In the series with myoplasty and fascioplasty, the shape of the residual limb was changed, the bone closing plate was absent, and the normalisation of intraosseous circulation did not occur even in remote lines. The preservation of the cylindrical shape of the residual limb, the normalisation of intraosseous circulation and the completion of the reparative process are indicators of favourable residual limb formation.